Sindrom Hepatopulmoner: [Hepatopulmonary Syndrome] - Kowiy Akbar; Isnu Pradjoko (Faculty of Medicine Universitas Airlangga, 2015)
Hepatopulmonary syndrome (HPS) is an important complication of liver disease on pulmonary organ; characterized by the triad of liver disease, pulmonary vascular dilatation, and oxygenation defect. Clinical signs and symptoms include dyspnea, platypnea, orthodeoxia, cyanosis, and clubbing finger. The underlying patophysiology involves abnormal vasodilation and angiogenesis in the pulmonary vascular bed, which leads to ventilation-perfusion mismatch, diffusion limitation to oxygen exchange, and arteriovenous shunting. This disorder is thought to be linked to liver cell injury, which stimulates release of endothelin-1 and results in increased expression of endothelin receptors on pulmonary endothelial cells, leading to upregulation of endothelial-nitric-oxide-synthase (eNOS) and subsequent increased production of nitric oxide (NO), ultimately causing vasodilation. Laboratory studies to establish diagnosis includes blood gas analysis and echocardiography, supported by radiology and pulmonary vascular cathetherization. Despite accumulated knowledge about the pathogenesis of HPS, currently there is still no established medical therapy, and liver transplantation remains the definitive treatment for this syndrome. Supportive therapy consists oflong term oxygen administration to prevent desaturation and alleviate dyspnea.